Pengaruh Kebijakan Dividen, Kebijakan Hutang Terhadap Harga Saham Dan Nilai Perusahaan Sebagai Variabel Intervening (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Lisnawati, Ika; Made, Anwar; Dianawati, Eris (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to determine the effect of dividend policy, debt policy on stock prices and company value as an intervening variable. In research using quantitative data types with secondary data sources. Samples obtained in this company were 31 manufacturing companies using purposive sampling method. Data collection techniques from books, internet, journals, and previous thesis. The variables used are dividend policy variables proxied with dividend payout ratio (DPR), and debt policy proxied debt to equity ratio (DER) as an independent variable, stock prices are proxied by Price Earning Ratio (PER) as the dependent variable, and company value Price book value (PBV) is proxied as an intervening variable. Data analysis techniques use the path test (path). The results of this partial research show that dividend policy (DPR) and debt policy (DER) have a significant positive effect on company value (PBV), company value (PBV) and dividend policy (DPR) which have a significant positive effect on stock prices (PER), and debt policy (DER) has no significant effect on stock prices. The results of the path test result show that the dividend policy (DPR) on the share price (PER) through the company value (PBV) has a significant indirect effect on the stock price (PER) and the debt policy (DER) on the stock price (PER ) through the company's value (PBV) there is no significant indirect effect on stock prices (PER).